Simulation of dynamic interactions of the earth–air heat exchanger with soil and atmosphere for preheating of ventilation air - Gan, Guohui (Elsevier, 2015)
Earth–air tunnel ventilation is an energy efficient means of preheating and cooling of supply air to a building. Due to changing soil and atmospheric conditions and the consequent changes in heating and cooling loads of a building during operation, an earth–air heat exchanger interacts with the environments and the performance varies with the conditions. A computer program has been developed for modelling of coupled heat and moisture transfer in soil and for simulation of the thermal performance of an earth–air heat exchanger for building ventilation, taking account of dynamic variations of climatic, load and soil conditions. The importance of dynamic interactions between the three media – heat exchanger, soil and atmosphere – is illustrated from the comparison of the heat transfer rates and supply air temperature through the heat exchanger under continuous and intermittent operation in heating seasons. It is shown that neglecting the interactions between any two or all three media would significantly over or under predict the heat transfer rate and air temperature. Neglecting the interactions between the heat exchanger, soil and ventilating air would over predict the thermal performance of an earth–air heat exchanger whereas neglecting the interactions between the soil surface and atmosphere would fail to produce reliable data for long term operational performance of the earth–air heat exchanger installed in shallow ground. The level of over-prediction could be larger for intermittent operation than for continuous operation.